Chemical speciation, human health risk assessment and pollution level of selected heavy metals in urban street dust of Shiraz, Iran. (October 2015) - Keshavarzi, Behnam; Tazarvi, Zahra; Rajabzadeh, Mohammad Ali; Najmeddin, Ali
Abstract: The distribution, pollution level, sources and health risk of Hg, As, Cd, Cu, Cr, Ni, Mn, Fe, Pb, Sb and Zn in urban street dust were investigated. X-ray diffraction analysis of dust samples shows that the mineralogy of airborne dusts is dominated by calcite, dolomite and quartz. The total concentration of trace elements across the sampling sites ranged from 36.8 to 234.3 mg kg −1 for Pb, 0.004–4.504 mg kg −1 for Hg, 160.9–778.3 mg kg −1 for Zn, 245–652 mg kg −1 for Mn, 39.4–117.9 mg kg −1 for Ni, 31.6–105.9 mg kg −1 for Cr, 49.8–232.5 mg kg −1 for Cu, 5.3–8.6 mg kg −1 for As, 0.31–0.85 mg kg −1 for Cd, 0.76–9.45 mg kg −1 for Sb, and 16, 300–24, 900 mg kg −1 for Fe. The enrichment factor results reveal the following order: Cu > Hg > Sb > Zn > Pb > Ni > Cr > As > Mn > Cd > Fe. Among the measured elements, the highest mobility factor belongs to Pb (79.2%), Hg (74.6%), Zn (64.1%) and Mn (56.4%). According to the calculated Hazard Quotient (HQ) and Hazard Index (HI), special attention should be paid to Hg, Pb, Zn, and Mn in the street dusts of Shiraz. Multivariate statistics indicate that traffic, natural soil particles and industrial activities are likely to be the main sources of heavy metals in Shiraz street dusts. Highlights: This study assesses a comprehensive environmental risk of urban trace metal pollution. This study evaluates mineralogy and human health risk combined with the speciation of trace metals. Calcite, dolomite and quartz are main mineralogical components of dust. This study points the critical contaminated metals that need to be paid special attention.